2004
DOI: 10.1007/bf03249521
|View full text |Cite
|
Sign up to set email alerts
|

Relationships among perceived competence, intrinsic value and mastery goal orientation in English and maths

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 54 publications
0
13
0
1
Order By: Relevance
“…Moreover, it has been appeared as one of the most important approaches in order to understand the students' achievement motivation in the recent years (Midgley et al, 1998). According to Cocks and Watt (2004), the importance of this issue has been reflected "in revisions to the instruments used to assess students' goals" (p.82). Similarly, Deemer (2004) thought of achievement goal theory as "the predominant theory of motivation in the educational psychology literature" (p.13).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, it has been appeared as one of the most important approaches in order to understand the students' achievement motivation in the recent years (Midgley et al, 1998). According to Cocks and Watt (2004), the importance of this issue has been reflected "in revisions to the instruments used to assess students' goals" (p.82). Similarly, Deemer (2004) thought of achievement goal theory as "the predominant theory of motivation in the educational psychology literature" (p.13).…”
Section: Introductionmentioning
confidence: 99%
“…First, classroom environment may influence learning goals. In particular, research suggests challenging tasks, methods of questioning, and classroom goal structure may encourage the development of mastery goals (Cocks & Watt, 2004;Morrone, Harkness, D'Ambrosio & Caulfield, 2004;Wolters, 2004). In a study of PSTs in particular, Morrone et al (2004) showed that when instructors structured their dialog and classroom discourse in order to support higher-order thinking, many of the PSTs developed mastery goals.…”
Section: How Motivational Profiles Develop Over Timementioning
confidence: 96%
“…And Margo recalled, "[my third grade math teacher] just was like I really want you guys to do really well on this exam so if you guys all get like an A or a B, I'll dance on my desk" (Interview 1). The link between learning goals and verbal persuasions is particularly interesting given that previous research has focused on support and encouragement as sources of learning goals (Cocks & Watt, 2004;Summers, 2006) but has not specifically focused on verbal persuasions.…”
Section: Verbal Persuasionsmentioning
confidence: 98%
See 1 more Smart Citation
“…It appears that competence beliefs, enjoyment (intrinsic value), and utility value would positively reinforce each other (Chouinard, Karsenti, & Roy, 2007;Cocks & Watt, 2004;Wilson et al, 2008). While the achievementrelated outcomes are employed as the final destination of this achievement-motivational theory, a more realistic picture would include reciprocal relationships (Marsh & Martin, 2011) among these constructs especially when developmental perspectives (Wigfield & Eccles, 2002) are taken into account.…”
Section: Enjoyment Competence Value and Achievementmentioning
confidence: 99%